A classification for macroscopic charcoal morphologies found in Holocene lacustrine sediments. (December 2014) - Mustaphi, Colin J. Courtney; Pisaric, Michael F.J.
Macroscopic charcoal analysis of lake sediment stratigraphies is a widely used approach to reconstruct past biomass burning patterns of ecosystems. The development of fire records often relies on a single quantification method of charcoal in a sediment subsample; however, recent studies have shown that additional paleoecological information can be obtained by classifying charcoal morphologies. The morphologies and diagnostic features of charcoal yields information about fuel sources, fire type, and charcoal taphonomy, and can aid in calibrating sediment records to known historical fires. This additional information enhances paleoecological inferences by providing more paleoenvironmental information than studies of total charcoal as the only metric. Here we present a classification of 27 macroscopic charcoal morphologies observed in Holocene sediments of lakes located in the mixed-conifer forests of southeastern British Columbia, Canada. This classification system builds on other morphological classifications that have been previously utilized, but is more inclusive of the morphological variability observed and is flexible to modification for use when applied to other study settings. The morphological classification presented here was developed following the observation of >100, 000 macroscopic charcoal fragments >150 µm. This paper focuses on the observed morphological classes, their identification, potential fuel sources, and the morphotype assemblage stratigraphy from one site as an example. The charcoal assemblages varied throughout the mid-to-late Holocene contemporaneously with known regional scale hydroclimatic changes in British Columbia. Major changes in fire frequency were also concomitant with morphotype assemblage changes. Future work focusing on linking fuel types with charcoal morphotypes, post-fire observations of charcoal taphonomy, and the analysis of multiple attribute charcoal data sets from a variety of ecosystems will improve our understanding of biomass burning and long-term fire ecology.